Topological valley photonics : physics and device applications - Xue, Haoran (2022)
Topological photonics has emerged as a promising field in photonics that is able to shape the science and technology of light. As a significant degree of freedom, valley is introduced to design and construct photonic topological phases, with encouraging recent progress in applications ranging from on-chip communications to terahertz lasers. Herein, the development of topological valley photonics is reviewed, from both perspectives of fundamental physics and practical applications. The unique valley-contrasting physics determines that the bulk topology and the bulk-boundary correspondence in valley photonic topological phases exhibit different properties from other photonic topological phases. Valley conservation allows not only robust propagation of light through sharp corners, but also 100% out-coupling of topological states to the surrounding environment. Finally, robust valley transport requires no magnetic materials or the complex construction of photonic pseudospin and, thus, can be integrated on compact photonic platforms for future technologies.